VARIANTS OF THE BATAK KINSHIP SYSTEM - ayuni, vidya fani; Wardana, Dwi Safira; Nafisa, Raudhatun (Universitas Lambung Mangkurat, 2025)
The kinship legal system is an important part of social life, regulating relationships between individuals in a family or relatives, either through the father's lineage (patrilineal), mother's lineage (matrilineal), or both (bilateral), and through marriage bonds. This system not only creates patterns of social relationships, but also forms new groups rooted in the culture of the community, while also playing a role in preserving and passing on cultural values to the next generation. The purpose of this study is to identify, analyze, and understand the kinship legal system in Indonesian society, especially related to the role of culture, family structure, and existing social dynamics. Specifically, this study also focuses on the kinship legal system in the Batak ethnic community, exploring the diversity of kinship patterns applied, and exploring its implications for social integration, cultural preservation, and the continuity of Batak ethnic traditions. This research method uses a qualitative approach. This research is in the form of a case study, which was chosen to examine a case with clear boundaries. The results of the study show that the dominance of the kinship system in a particular society can be explained through several complex factors. First, strong local traditions and cultures establish this system as an integral part of community identity. Second, the economic structure, especially in agrarian societies, creates the need for a strong kinship network for resource management and social support. Third, the social interests that arise from interdependence among family members facilitate solidarity and cooperation. Fourth, customary law remains relevant and serves as a conflict resolution mechanism that is more acceptable to society than formal law.